Birth and evolution of "social studies" in Myanmar: dramatic changes in contents and approaches - Yoshitaka Tanaka (Emerald Publishing, 2023)
Purpose - This research clarifies the birth and evolution of "Social Study" in Myanmar through analyzing the differences of contents and approaches between "Social Studies" under the military administration and that under the recent democratic administration. Design/methodology/approach - The author obtained "Social Studies" textbooks that were used both in the past as well as in present day and translated them into English. The textbooks' contents were analyzed in detail while referring Japanese and American "Social Studies" textbooks. Specifically, the author focused on the content structure of the textbooks and the learning objectives and approaches used. Each textbook was analyzed in accordance with the era in which they were used considering the social and political conditions at those times. In addition, the author clarified the necessary competencies for the people of Myanmar during the new era through discussions with many Myanmar educators. Based on this research, the author advised the Ministry of Education on the content of new "Social Studies" textbooks and supported their development. Findings - The idea of child-centered education introduced under the military administration was further strengthened in the recent new "Social Studies" textbooks allowing students to learn by tapping into their interests and also encouraging deep thinking and creativity. This approach changed their learning from memorization without deep thinking in the past to contemplating things and creating new ideas. Originality/value - The findings can provide curriculum developers and educators in other countries with a broad direction on how to reform "Social Studies" and related subjects curricula and textbooks in their own countries in the future.